The Effectiveness of Beelinguapp Mobile Application to Improve English Speaking - Arumsari, Arumsari; Octaviani, Saly Kurnia; Vinahapsari, Cinthia Annisa (Universitas Pahlawan Tuanku Tambusai, 2025)
Creative learning media in innovative education should be sufficient to motivate students to learn English, especially to improve English speaking skill. One of application-based learning media that can make second language learners interested in learning English-speaking skills is the Beelinguapp. This research aims to improve English speaking skill for 2nd semester college students of STMIK Sinar Nusantara Surakarta by using Beelinguap mobile application. This study used quantitative method. This study also used a pre-experimental method having pre-test and post-test. This research focused on 30 students of Bachelor’s degree from Informatics program in academic year 2023/2024. In the result of study, the average of the pre-test score is 49.33 and the result of the average score of the post test is 70.4. It can be concluded that learning media using Beelinguapp can improve students' English-speaking skills because there is an increase of 0.43% from the pre-test to post-test.